2012
DOI: 10.3109/13697137.2012.727199
|View full text |Cite
|
Sign up to set email alerts
|

Hot flushes still occur in a population of 85-year-old Swedish women

Abstract: Results: About 16% (n=29) of the women experienced hot flushes during the day and/or during the night and 6.5% (n=12) of the women were currently using hormone therapy (HT).Almost 1/10 (n =17) out of all responding women were very to moderately distressed by their hot flushes. Discussion:Our results confirm and extend previous knowledge based on studies of younger postmenopausal women in showing that menopausal symptoms still occur in elderly women.We found that while the prevalence of menopausal symptoms decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“…In some women, VMS persist on average 7.4 years and sometimes for more than 10 years. In a study of Swedish women aged older than 85 years, 16% reported hot flashes at least several times per week (Vikstrom et al 2013). HT can be considered for prevention of osteoporosis in women aged 65 years and older at elevated risk for fracture when bothersome VMS persist or when HT remains the best choice for QoL reasons or because of lack of efficacy or intolerance of other osteoporosis-prevention therapies.…”
Section: Hrt In Older Women: Is It Ever Too Late?mentioning
confidence: 99%
“…In some women, VMS persist on average 7.4 years and sometimes for more than 10 years. In a study of Swedish women aged older than 85 years, 16% reported hot flashes at least several times per week (Vikstrom et al 2013). HT can be considered for prevention of osteoporosis in women aged 65 years and older at elevated risk for fracture when bothersome VMS persist or when HT remains the best choice for QoL reasons or because of lack of efficacy or intolerance of other osteoporosis-prevention therapies.…”
Section: Hrt In Older Women: Is It Ever Too Late?mentioning
confidence: 99%
“…Близько 10% жінок відчувають вазомоторні симптоми більше 10 років після настання менопаузи. Так, вазомоторні симптоми продовжують відчувати 16% 85-річних жінок [25].…”
Section: діагностика і диференційна діагностика клімактеріюunclassified
“…Близько 10% жінок відчувають вазомоторні симптоми більше 10 років після настання менопаузи. Так, вазомоторні симптоми про-довжують відчувати 16% 85-річних жінок [25].…”
Section: тривалість симптомівunclassified